A role for the TIM‐3/GAL‐9/BAT3 pathway in determining the clinical phenotype of multiple sclerosis. Issue 11 (4th August 2014) - Saresella, Marina; Piancone, Federica; Marventano, Ivana; La Rosa, Francesca; Tortorella, Paola; Caputo, Domenico; Rovaris, Marco; Clerici, Mario
Abstract : T‐cell immunoglobulin and mucin domain 3 (Tim‐3) ligates galectin‐9 (Gal‐9); this process, resulting in the inhibition of Th 1 responses and in the apoptosis of antigen‐specific cells, is hampered by binding of the molecular adaptor human leukocyte antigen B (HLA‐B)‐associated transcript 3 (Bat3) to the intracellular tail of Tim‐3. Apoptosis of myelin basic protein (MBP)‐specific T lymphocytes correlates with reduced rates of disease progression in multiple sclerosis (MS). We extensively analyzed the Tim‐3/Gal‐9/Bat3 pathway in 87 patients with a diagnosis of stable relapsing‐remitting MS (RRMS), primary progressive MS (PPMS), or benign MS (BEMS), as well as in 40 healthy control (HC) subjects. Results showed that MBP‐specific CD4 + Tim‐3 +, CD4 + /Gal‐9 +, and CD4 + /Tim‐3 + /AV + (apoptotic) T lymphocytes were augmented in the BEMS group, whereas CD4 + /Bat3 + and CD8 + /Bat3 + T lymphocytes were increased and CD4 + /Tim‐3 + /AV + T cells were reduced in the PPMS group (>2 fold and P <0.05 in all cases). Blocking the Tim‐3/Gal‐9 interaction with specific mAb reduced T‐lymphocyte apoptosis and augmented production of IFNγ and IL‐17 in the BEMS, RRMS, and HC groups, but not in the PPMS group. The Tim‐3/Gal‐9 interaction favors apoptosis of MBP‐specific T lymphocytes in BEMS; this process is reduced in PPMS by the up‐regulation of Bat3. Therapeutic interventions aimed at silencing Bat3 could be beneficial in MS.—Saresella, M., Piancone, F., Marventano, I., La Rosa, F., Tortorella, P., Caputo, D., Rovaris, M., Clerici, M., A role for the TIM‐3/GAL‐9/BAT3 pathway in determining the clinical phenotype of multiple sclerosis. FASEB J. 28, 5000–5009 (2014). www.fasebj.org